Alokasi Waktu Pekerja Perempuan Pada Sektor Informal Perdagangan di Desa Dangin Puri Klod Denpasar Timur - Sari, Mia Komala; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 2, Desember 2012, 2012)
This study aims to determine how the time allocation of women’s labour in the informal sector of trading, and explain the variables that influence simultaneously and partially. Research was conducted in the Village of Dangin Puri Klod subdistrict of Denpasar Timur and sampling technique was used by purposive sampling. Analysis technique used multiple linear regression. The results of hypothesis testing simultaneously can be known that household income, education level, household dependents, and presence of children under five year affect women’s labour time allocation. Partially, the variables of household income and children under five years had negative and significant impact on women’s labour time allocation. While the level of education and household dependents affected positive and significant.
Keywords: time allocation , women labour , informal sector